Beschleunigte Simulation des Laserstrahlumformens von Aluminiumblechen - Pitz, Indra (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)
Due to the high computing effort the finite element simulation of laser beam forming still poses a great challenge. In this thesis a methodology is presented estimating the lower limit of the essential number of elements. In combination with a transient discretisation this methodology leads to a decrease of the computing effort and thus to a significant acceleration of the FE-simulation of laser beam forming under application of the temperature gradient mechanis

Modelle zur beschleunigten Simulatin des Laserstrahlumformens im Makrobereich - Pitz, Indra; Otto, Andreas (Simulation and Visualization 2008 - Proceedins of the 2008 Simulation and Visualization Conference, 2008)
LFT Import::2019-08-05 (1517)

Modelling of Laser BEam Forming of Large Sheet Metal Parts - Pitz, Indra; Otto, Andreas; Geiger, Manfred (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1436)

Simulation of Laser Beam Formng of Large Aluminium Plates - Pitz, Indra; Otto, Andreas (Thermal Forming and Welding Distortion - Proceedings of the IWOTE 2008: International Workshop on Thermal Forming and Welding Distortion, 2008)
LFT Import::2019-08-05 (1523)

Simulation of the Laser Beam Forming Process with Moving Meshes for Large Aluminium Plates - Pitz, Indra; Otto, Andreas; Schmidt, Michael (Physics Procedia, 2010)